Analytical Properties of the Generalized Heat Matrix Polynomials Associated with Fractional Calculus. (9th June 2021) - Abdalla, Mohamed; Boulaaras, Salah Mahmoud
Abstract : In this paper, we introduce a matrix version of the generalized heat polynomials. Some analytic properties of the generalized heat matrix polynomials are obtained including generating matrix functions, finite sums, and Laplace integral transforms. In addition, further properties are investigated using fractional calculus operators.